Androgens improve ovarian follicle function impaired by glucocorticoids through an androgen-IGF1-FSH synergistic effect - Gao, Lingyun; Gao, Hongna; Wang, Wenjun (Frontiers in Endocrinology, 2022)
High concentrations of glucocorticoids caused by chronic stress are known to affect ovarian function and cause diminished ovarian reserve. Androgens are essential for early-stage ovarian follicle development, but the effects and mechanisms of androgens on follicle development under chronic stress remain unclear. In this study, we aim to investigate the effects of high concentrations of glucocorticoids on the function of in vitro cultured ovarian cells and mouse early-stage ovarian follicles, and to validate the hypothesis that androgen-IGF1-FSH synergistic signaling helps to ameliorate the damage caused by high concentrations of glucocorticoids. KGN cells (human granulosa cell line) and mouse primary cells were treated with different concentrations of glucocorticoids, and the cell proliferation, apoptosis, and sex hormone secretion were detected. The effects of glucocorticoid and androgens on IGF1 receptor (IGF1R) and FSH receptor (FSHR) expression in KGN cells were detected by Western-blot. Steroidogenic synthase expressions under androgens and androgen-IGF1-FSH combination treatment were examined by qPCR after low- and high-concentrations of glucocorticoids manipulation. The mechanism of androgen regulation of IGF1R and FSHR was explored by siRNA and CHIP-qPCR. Damage of glucocorticoids and the treatment effects of androgens were further validated in mouse ovarian follicles cultured in vitro. The results demonstrated that prolonged treatment of high dose glucocorticoids reduced cell viability of granulosa cells, inhibited their sex hormone secretion, and impaired their sensitivity to IGF1 and FSH signaling by affecting IGF1R and FSHR functions. Androgens at an appropriate dose range improved early-stage follicle development and their hormone secretion under high dose glucocorticoids treatment, which was related with the increased the transcription of Igf1r and Fshr. This work showed that excessive glucocorticoids impaired ovarian function and validated that balanced concentrations of androgens synergized with IGF1and FSH to improve the function of early-stage ovarian follicles under conditions of chronic stress.